The Effects of Credit, Liquidity, and Operational Risks on GCC Bank Financial Stability: Moderating Role of Board Size - Alsulmi, Fatima; Mahmood, Rosli; Sapar, Resul (Advances in Social Sciences Research Journal, 2024)
This paper examined the impact of three types of bank risk: credit, liquidity, and operational risk on bank financial stability. It also examined the moderating role of board size and board frequency meetings. It also investigated the macroeconomic factors such as GDP growth and inflation and their influence on bank financial stability. A sample of listed banks in GCC stock exchanges from 2014 to 2022 using a panel data analysis. The findings highlighted that credit and operational risk significantly impact a bank’s financial stability, but liquidity risk is unrelated to the bank’s financial stability. In addition, GDP and the Covid-19 pandemic had a negative impact on bank financial stability. Board size significantly moderates relationships between credit risk, operation risk, and bank financial stability.